Application of spectroscopic methods for investigation of the course of poly(sodium acrylate) crosslinking with use of different crosslinking agents - Grabowska, B.; Holtzer, M. (Polimery, 2022)
The course of the crosslinking process of poly(sodium acrylate) (PAS), used as a binder for molding sands made of olivine sand as a matrix, was studied with use of FT-IR and Raman spectroscopic methods. Three methods of hardening were applied: classical, with use of Ca(OH)2+CO2 system, and in more innovative way by microwave or UV radiation. It was found, on the basis of analysis of spectra obtained (Fig. 1-6), that the PAS crosslinking agent significantly influenced the reaction course. Namely, the Ca(OH)2+CO2 system caused ionic bonds' formation while microwave radiation led to formation of covalent bonds with part of silanolic groups of matrix surface layer. In case of hardening by UV radiation, the product of complicated crosslinked structure occurs because of the reactions of active radicals formed in the polymer. Compressive strength (Rcu) of molding sands hardened with the methods mentioned above has been evaluated (Fig. 7). The samples hardened with microwaves showed the highest values of Rcu.